Quartz sand separation and purification process system - LIU GUANDONG; QIN ANSHAN (2015)
The invention discloses a quartz sand separation and purification process system comprising steps as follows: ore dressing; ore washing; calcination; water quenching; crushing; screening; quartz sand cleaning; feeding: firstly, opening a quartz sand discharging valve, adding high-purity hydrochloric acid, then opening an acid solution discharging valve, continuously mixing an acid solution and quartz sand to form a hot acid-containing material, automatically controlling the temperature, stirring the material for a reaction for 20-30 min, performing precipitation, removing the acid solution, adding a proper amount of ultrapure water, and performing stirring and washing; acid pickling; acid removal; drying: placing the quartz sand into a drying plate, setting the temperature of a drying oven at 180 DEG C, adjusting the drying oven to be controlled automatically, increasing the temperature to the set temperature, keeping the temperature for 3 h, stopping heating, opening a door to take out the dried material after 1 h, and performing the next procedure; magnetic separation: evenly pouring the dried material into a magnetic separator for magnetic separation. With the adoption of the system, film iron or impregnated iron on surfaces of quartz sand particles can be removed, and the fineness of the quartz sand can be increased; in addition, continuous production of quartz sand acid pickling and purification is realized on the premise that the high-quality purification of products is guaranteed.